O método de composição de O amanuense Belmiro: um problema histórico, crítico e estético - Alex Alves Fogal (2011)
The proposal of this work is to develop a study about the novel O amanuense Belmiro (1937) by Cyro dos Anjos, whereof a triple front, It means, the aim is to establish an interpretation line able to provide a reflection about the problem of literature history, critic and aesthetic. In what concerns about the historiographical point, well look forcomprehending in what ways the mineiro writer narrative uses to connect to the known theme about the division between the social novel and the psychological novel of the thirties, beyond that, we will try to understand in which ways this novel fit in that period. In relation to the literary critic, the intention is to perform an analysis about what the representative studies said about the method used for the composition of the book and in which ways they place this book on Brazilian literature scenario. In what concerns the aesthetic problem, it will be develop a formal analysis about the literary configuration of the romance to try to prove that O amanuense Belmiro can not be definitely framed in neither of the two strands of the second modernist phase, once it is structured in a method of ambiguous narrative.